Synthesis and biological evaluation of fluoro-substituted 3, 4-dihydroquinazoline derivatives for cytotoxic and analgesic effects. Issue 17 (1st September 2017) - Kim, Jin Han; Jeong, Hui Rak; Jung, Da Woon; Yoon, Hong Bin; Kim, Sun Young; Kim, Hyoung Ja; Lee, Kyung-Tae; Gadotti, Vinicius M.; Huang, Junting; Zhang, Fang-Xiong; Zamponi, Gerald W.; Lee, Jae Yeol
Graphical abstract: Abstract: As a bioisosteric strategy to overcome the poor metabolic stability of lead compound KYS05090S, a series of new fluoro-substituted 3, 4-dihydroquinazoline derivatives was prepared and evaluated for T-type calcium channel (Cav 3.2) block, cytotoxic effects and liver microsomal stability. Among them, compound8h (KCP10068F) containing 4-fluorobenzyl amide and 4-cyclohexylphenyl ring potently blocked Cav 3.2 currents (>90% inhibition) at 10 μM concentration and exhibited cytotoxic effect (IC50 = 5.9 μM) in A549 non-small cell lung cancer cells that was comparable to KYS05090S. Furthermore, 8h showed approximately a 2-fold increase in liver metabolic stability in rat and human species compared to KYS05090S. Based on these overall results, 8h (KCP10068F) may therefore represent a good backup compound for KYS05090S for further biological investigations as novel cytotoxic agent. In addition, compound8g (KCP10067F) was found to partially protect from inflammatory pain via a blockade of Cav 3.2 channels.